Measurement of Radiation Dose in CT Scan and Fluoroscopy Area at dr. Saiful Anwar General Hospital Malang - Novita Roysida (Jurnal VOK@SINDO, 2016)
Radiation dose measurement in diagnostic radiology is considered to be a critical factor for optimizing radiation protection to the healthcare practitioners, the patients and the public. This paper presents an overview of average radiation dose measurement in public area around CT Scan and Fluoroscopy area. The recommendation of critical radiation dose from BAPETEN is bellow 50 mSv/ year for healthcare practitioners and below 5 mSv/year for public area. The measurement of radiation dose has been done outside the CT Scan and fluoroscopy room using surveymeter.